Villa Nueva opening ceremony - Unknown:::Creator::::::::::::
Photograph shows what is possibly the opening ceremony for Villa Nueva. Men and women are sitting in chairs on an outdoor patio while listening to a man standing at a podium speak. There are four professional cameramen in the back of the crowd.